Persepsi, Motif, dan Perubahan Perilaku Jama’ah Umrah pada Biro Travel Haji dan Umrah di Kota Kediri - Adlan, Muhamad Aqim (Tribakti: Jurnal Pemikiran Keislaman, 2021)
The purpose of this study is to determine the perceptions, motives, and changes in the behavior of the Umrah pilgrims at the Haj and Umrah travel agencies in Kediri. This is based on the problem of waiting time for the pilgrimage to depart. So that some Muslims chose Umrah as an alternative to immediately go to Mecca. However, this condition provoked some irresponsible travel agencies to take a chance. This study uses a qualitative research method with the type of case study research. The findings in this study indicate that: First, the perception of Umrah pilgrims on the existence of an Umrah travel agency is still very much needed today because its existence is very helpful in facilitating the process of carrying out the Umrah pilgrimage. Second, there are two different motives for performing the Umrah pilgrimage within the Umrah congregation, namely the motive for worship and others. Third, Umrah has an impact on better behavior than before.